2012
DOI: 10.3113/fai.2012.1087
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Changes of Ankle Joint after Total Knee Arthroplasty

Abstract: After total knee arthroplasty, arthritis developed or progressed in the ankle of many cases radiographically. In particular, when the preoperative talar tilt increased medial to the ankle or the postoperative correction angle was large, the incidence of arthritis in the ankle joint increased. The authors recommend more cautious follow-up on the symptoms of the ankle joint after total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 15 publications
4
91
2
Order By: Relevance
“…This redistribution of pressure over a smaller surface of the talar dome could have long‐term implications for the biomechanics of the ankle. This is especially germane considering that previous studies have linked realignment procedures about the knee (both HTO and TKA) with the development and progression of ankle OA or ankle pain . It seems likely that the subtalar joint plays an important role in maintaining adequate alignment and force distribution .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This redistribution of pressure over a smaller surface of the talar dome could have long‐term implications for the biomechanics of the ankle. This is especially germane considering that previous studies have linked realignment procedures about the knee (both HTO and TKA) with the development and progression of ankle OA or ankle pain . It seems likely that the subtalar joint plays an important role in maintaining adequate alignment and force distribution .…”
Section: Discussionmentioning
confidence: 99%
“…A change in the ankle tilt after HTO was deemed as the most likely cause of pain due to possible changes in the contact area of the ankle joint and the patient was treated with a corrective supramalleolar osteotomy. Other studies have shown that total knee arthroplasty (TKA), in which lower limb alignment is also corrected, results in variations in hindfoot alignment . In a series of 142 TKA cases, Lee et al showed that 22% had newly developed or progressive ankle OA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that many patients complained of pain in the ankle after total knee arthroplasty, and we surmised that a change in the alignment of the lower extremity caused by a relatively large knee varus correction angle might be one of the reasons for the discomfort. Jung Hee Lee et al [3] reported that 35.2% of patients had radiographic change in ankle joint after conventional total knee arthroplasty (TKA), and this may be an early sign of ankle osteoarthritic change [3].…”
Section: Resultsmentioning
confidence: 99%
“…The postoperative knee joint obliquity can be compensated by the ankle joint [8,[15][16][17][18]. The capacity of compensation was suggested to be determined by the mobility of the subtalar joint [17,19], which differs by individual.…”
Section: Introductionmentioning
confidence: 99%